HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP PENGGUNAAN JAMU TOLAK ANGIN DALAM KEMASAN YANG DI JUAL PEDAGANG JAMU GEROBAK KECAMATAN MEDAN JOHOR - Masrah, Masrah; ZULFA ISMANIAR FAUZI; Chairunnisa Rangkuti (Poltekkes Kemenkes Medan, 2025)
Jamu is a traditional medicine, resulting from the experience and culture of an area that continues to develop and change. Even though modern medicine is developing, the consumption of herbal medicine has not been abandoned by Indonesian people and is still frequently consumed, one of which is Tolak Angin. The purpose of this study was to determine the correlation of people's knowledge and attitudes towards the consumption